THE IMPACT OF PREFORMANCE EVALUATION PROCESS ON HEALTHCARE EMPLOYEES AS A FACTOR FOR MOTIVATION AND QUALITY OF THEIR WORK - Georgievska Cvetanovska, Mila; Trpeski, Predrag (Institute of Knowledge Management - Skopje, 2018)
The performance evaluation process is used to conduct an objective assessment of the performance and the effectiveness of the employees, the compliance with the organizational values and hierarchy and the achevement of the standards of the organization. The employee performance evaluation is an exceptionally important segment in healthcare organizations. The managers (directors) of the healthcare organizations have to recognize the employees that efficiently complete their tasks, detect the need and the type of training necessary to improve their performance and adequately reward the most prominent employees. Taking into account the relevance of the topic, the subject of research in this papers is precisely the analysis of the performance appraisal of the employees, as a process that should help obtaining a clear picture of how successfully the tasks of a given position are performed and how much they contribute to achieving the strategic goals of the organization. Hence arises the problem of this research, which is the absence of a quality system for evaluation and assessment of the performance of the healthcare workers. Two research goals have been pursued, both scientific and practical. The scientific goal of the research is to provide quality performance evaluation of the healthcare workers, which leads to faster development of the organization and sustainable efficiency of the market, whereas the practical goal of the research is to utilize the obtained results in the creation of an efficient system for evaluating the performance of the healthcare workers who will integrate the quality work standards, thereby improving the motivation and the quality of work. The relevance of the topic will be explored and proven by defining a hypothesis that reads: If a health care organization adopts a quality system for evaluating the work of its healthcare workers, then the healthcare employees will strengthen their skills which will lead to increased motivation and work quality. To prove the hypothesis, an empirical research was conducted using a standardized instrument, i.e. a questionnaire containing 10 statements and a Likert scale: strongly agree, partly agree and disagree. The questionnaires contained closed-ended questions whereby the respondents could choose one of the answers offered. The survey was conducted in 2 private healthcare organizations in December 2017. The representative sample includes 73 doctors and 27 nurses/orderlies. In the process of analyzing the findings of the research, a deductive method, comparison method and a method of objectivity and relevance were applied. In the conclusion of the papers, on the basis of the obtained results, guidelines will be proposed for improvement and implementation of a quality performance evaluation system in the private and public health care.
Keywords: evaluation, performance, healthcare organizations, quality, motivation